Driven to extinction : the impact of climate change on biodiversity - Pearson, Richard G. (Richard Grenville), 1977-; American Museum of Natural History (New York : Sterling, 2011)
Explores the possible effects of global warming and climate change on more than a million species around the globe.
'American Museum of Natural History.'
Includes bibliographical references (p. 226-254) and index.
Keywords: Climatic changes -- Environmental aspects; Biodiversity; Bioclimatology; Extinction (Biology); Biodiversity conservation